Praktek Pencegahan Penularan Malaria pada Balita di Puskesmas Kabukarudi Sumba Barat - Florentina Gehand Wau; Honey I. Ndoen; Soleman Landi (Universitas Nusa Cendana, 2019)
Malaria is the infection disease wich is caused by parasite genus plasmodium which is infected eritrosit. Kabukarudi Health Center has the highest cases of malaria in West Sumba. Malaria on 2015 were approximately 240 cases of which most cases happend in children under five years old. The research aims to to know the effect of nutrient, application of repellent and the usage of mosquito nets in Kabukarudi Health Center in Lamboya District of West Sumba. The research was case control study with the sample of 45 children infected by malaria and 45 uninfected children. The research instrument used was questionnaire and data were analyzed by Chi-Square. The result showed that the nutrient status had no effect on Malaria (p=0,383; OR=2), while repellent application (p=0, 007., OR=4,047) and mosquito net usage (p=0, 000; OR=6,484), influenced malaria cases in children. Health workers need to deliver information about the benefits of repellent and usage of mosquito nets to communities, especially to mother to help prevent malaria in children.